Marketing communication effectiveness strategies at Etiqa Takaful in Kota Kinabalu / Haslina Hasan - Hasan, Haslina (2009)
This study was conducted to identify the effectiveness of marketing communication strategies at Etiqa Takaful. This study also to identify the effectiveness of current marketing communication activities of Etiqa. Marketing is everything a company does to acquire customers and to maintain relationship with them. Therefore this study will help a company to enhance their marketing communication strategies to make Etiqa is the first of Takaful and Insurance company. During my practical at Etiqa Takaful ,about 120 questionnaires distributed to respondent at zone 1 in Kota Kinabalu. Descriptive research was used to obtain the data. The sampling technique that was used in conducting this study is convenience sampling. It is attempts to obtain a sample convenience element. At the end of study , recommendation are made in order to help company to enhance and improve their effectiveness marketing communication . Therefore the company will achieve their target and objective.